Phytochemical Content and Antioxidant Capacities of Hydrophilic Extracts of Vegetables Commonly Consumed In the Philippines - Manaois, Rosaly V.; Zapater, John Edward I.; Morales, Amelia V. (2020)
To provide data on the potential of local plant foods as sources of phytochemicals for human health, this study evaluated the phenolic content and antioxidant capacity of locally cultivated vegetables, both in raw form and in a form that they are usually consumed. Hydrophilic extracts of raw and boiled forms of 47 locally cultivated vegetables were evaluated for their total phenolic content (TPC) and antioxidant capacities using the 2,2-diphenylpicrylhydrazyl (DPPH) and 2,2-azinobis(3-ethylbenzothiazoline-6-sulfonic acid)-diammonium salt (ABTS) assays. Results showed that the TPC of raw vegetables ranged 1.0?79.6 mg gallic acid equivalents (GAE) g?1, with the following vegetables having the highest values among the lot: turmeric > red coral lettuce > sweet potato tops ≥ chili leaves > jute > water spinach 1 > green eggplant > purple eggplant. Antioxidant capacities of raw samples determined by DPPH and ABTS assays ranged 0.6?380.6 µmol Trolox equivalents (TE) g?1 and 1.4-322.7 µmol TE g?1, respectively, with the following plants consistently displaying the strongest scavenging values among the lot: turmeric, red coral lettuce, sweet potato tops, jute, chili leaves, lowland water spinach, and purple eggplant. Boiling plant foods had variable effects depending on the material studied. The TPC and antioxidant capacities of the fruit samples eggplant, green pepper, and squash significantly increased (p < 0.05) after boiling, while those of chili leaves and squash flower decreased. Boiling generally reduced the antioxidant capacities but turmeric, lowland water spinach, and chili leaves consistently exhibited the highest TPC and antioxidant capacities in either form among the tested samples. Our findings signify that local vegetables may be sources of phenolics and other hydrophilic compounds with antioxidant properties.
Includes bibliographical references (pages 1056-1058)
Keywords: ABTS radical-cation scavenging activity; Antioxidants; DPPH radical scavenging activity; Phenolics